The Relationship Between Soil Layer Depth and Macro Nutrients N P K In Oil Palm Plantations In Sungai Tawar Village Tanjung Jabung Timur Regency - Hasriati Nasution; Suryanto Suryanto; Asmadi Saad (International Journal on Advanced Science, Education, and Religion, 2025)
Peatland characteristics are an important consideration in land management for agricultural development. As peat depth increases, nutrient availability and microbial activity tend to decline, while soil acidity (pH) increases. Thicker peat layers therefore have a significant influence on soil fertility. Oil palm (Elaeis guineensis Jacq.), originating from Nigeria in West Africa, is widely cultivated in Malaysia, Indonesia, Thailand, and Papua New Guinea. Oil palm plays a strategic role in national plantation development by creating employment opportunities, improving community welfare, and contributing substantially to national foreign exchange earnings, with Indonesia being one of the world’s major palm oil producers. This study was conducted at an oil palm plantation in Sungai Tawar Village, Geragai Subdistrict, East Tanjung Jabung Regency. The research was carried out over four months during 2024–2025. Soil analyses were performed at the Soil Laboratory, Faculty of Agriculture, Universitas Jambi. The study used a survey method with purposive random sampling. Observed parameters included groundwater table depth, soil organic carbon (C-organic), peat depth, macronutrient content (N, P, and K), and peat maturity. Observations were conducted on oil palm stands aged 11 and 16 years, with ten soil sampling replications for each plant age. Data interpretation to identify differences in soil depth and NPK content between oil palm ages was conducted using an independent t-test for C-organic content, N, P, and K levels, groundwater table depth, peat thickness, and peat maturity. The relationship between C-organic content and NPK was analyzed using simple linear regression. Results showed strong correlations between peat layer depth, groundwater level, and nitrogen availability, as well as between soil C-organic content and total nitrogen, available phosphorus, and total potassium across different oil palm ages.